Manajemen Pembelajaran Daring di Madrasah Aliyah Negeri 2 Samarinda - Ridha, Muhammad; Setyoningrum, Muthia Umi (Borneo Journal of Islamic Education, 2022)
MAN 2 Samarinda is designated as one of the leading MAN in Indonesia. The success of SMA 2 Samarinda is not only determined by the quality of its students, but this success is also obtained through a learning process that cannot be separated from the role of educators who are active in holding workshops, seminars and training. During the Covid-19 pandemic, teaching and learning activities were carried out online from home. Based on these conditions, researchers are interested in conducting research on online learning management at MAN 2 Samarinda. The research method used in this research is descriptive qualitative. Data collection techniques namely by observation, interviews, and documentation. The data analysis technique used is the Miles and Hubberman model. The data validation technique uses triangulation techniques. The results of research on online learning management at Madrasah Aliyah Negeri 2 Samarinda include three stages, namely planning, implementation, and evaluation. The planning includes making documents for 1 period of covid, the process of teaching and learning activities is carried out by the teacher 1 day at home and 1 day at the office with a schedule supported by learning media used such as e-learning madrasas, whatsapp, zoom meeting, telegram, google classroom, google forms, and so on. Learning is carried out online from Monday to Saturday from 08.00 am to 12.00 noon. The media used to connect with each other are madrasah e-learning, whatsapp, zoom meeting, telegram, google classroom, google form, and so on. Evaluation is carried out in 3 stages, namely evaluation conducted by the school principal per week, evaluation through meetings of all stakeholders with the BK per month, and evaluation by the teacher which is carried out after the subject is completed.